To Improve Total Knee Prostheses Performance Using Three-Phase Ceramic-Based Functionally Graded Biomaterials - Ayatollahi, Majid Reza; Davari, Mohammad Hossein; Shirazi, Hadi Asgharzadeh; Asnafi, Alireza (Frontiers in Materials, 2019)
One of the common issues that occur after total knee replacement surgery is the aseptic loosening. The problem usually occurs after about fifteen years from the surgery. The destructive effects of residual particles due to wear, the stress shielding effect, and micro-movements are the causative factors for this type of loosening. In this research, using the advantages of functionally graded biomaterials (FGBM), it is tried to design a prosthetic system that can reduce the above mentioned effects. For this purpose, the materials used in the most important part of the prosthesis system, i.e. the femoral part are redesigned so that the bioactivity between the prosthesis and bone, and the stress applied to the adjacent tissues increase simultaneously. In addition, to reduce the effect of wear at contact areas, wear-resistant biocompatible ceramics such as alumina and zirconia are used. The value of stress at bone-prosthesis interface and adjacent tissues is the most important parameters. Two types of three-phase ceramic-based FGBMs are recommended. The prosthesis with three-phase hydroxyapatite-titanium-zirconia has increased the average stress in the bone tissues around high risk areas up to 71.8% with respect to a commonly used Cr-Co prosthesis. The result for prosthesis with three-phase hydroxyapatite-titanium-alumina is up to 65% respectively. At bone-prosthesis interfaces, an increase of 92% in the stress for both zirconia-based and alumina-based is seen. Briefly, the recommended FGBMs can improve the bone-prosthesis performance in all desired indices.